Strategic Leadership of Islamic Boarding School Leaders in Student Organizational Management - Nita Linda; Musli; Ahmad Fikri (Journal of Educational Management Research, 2026)
This study aims to analyze leadership strategies in managing student organizations within Islamic boarding school contexts, focusing on planning, organizing, implementation, and supervision, as well as identifying supporting and inhibiting factors. A qualitative field study approach was employed. Data were collected through in-depth interviews, observations, and document analysis, and analyzed interactively using data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that leadership strategies are implemented through a participatory approach, characterized by clear role distribution, structured guidance, and educational evaluation mechanisms. These strategies contribute significantly to improving student discipline, independence, and overall organizational effectiveness. Supporting factors include strong leadership commitment and continuous supervision, while inhibiting factors involve limited managerial experience among student officers and tightly scheduled institutional activities. The study implies that effective student organizational governance requires structured mentoring, systematic leadership training for student officers, and continuous evaluation systems. These elements are essential to strengthening organizational capacity and fostering sustainable student leadership development within faith-based educational institutions.